Confirmatory factor analysis of an emotional intelligence scale - Wan Husin, Wan Nurul Izza; Santos, Angeli; Ramos, Hazel Melanie Ramos; Nordin, Mohamad Sahari (2012)
Despite the popularity of the concept of emotional intelligence (EI) in recent years, several researchers question the current emotional intelligence tests on many grounds including lack of construct validity and unstable factor structure. The present study investigates the factorial validity of the Wong and Law Emotional Intelligence Scale (WLEIS) and seeks to confirm the factorial validity of this scale in different context. Results from a confirmatory factor analysis (CFA) utilizing structural equation modeling techniques supported the four-factor structure of WLEIS. Meanwhile, the psychometrics features of WLEIS supported its feasibility as a sound and reliable instrument for emotional intelligence research.